Synergistic separation of yttrium ions in lanthanide series from rare earths mixture via hollow fiber supported liquid membrane - Ramakul, Prakorn; Supajaroon, Tossaporn; Prapasawat, Tatchanok; Pancharoen, Ura; Lothongkum, Anchaleeporn W. (My University, 2009)
Separation of yttrium ions from the mixture of rare earths in lanthanide series has been examined by a microporous hydrophobic hollow fiber supported liquid membrane. Cyanex 272 and TBP in kerosene are used separately as an extractant. Nitric acid solution is used as a stripping solution. Increasing the concentration of Cyanex 272 increases the percentages of extraction and stripping of yttrium from rare earths but slightly percentages are obtained by TBP. Interestingly, when TBP is added with Cyanex 272, the percentages of extraction and stripping increases. This is due to the synergistic effect of the extractants. Moreover, yttrium can be selectively extracted and stripped more than other lanthanide ions because the equilibrium constant decreases with an increase in atomic number or decreases with the ionic radius of the lanthanides. In other words, yttrium is separated selectively due to the smallest ionic radius while other lanthanides are separated with a decrease in ionic radius or an increase in atomic number. © 2009 The Korean Society of Industrial and Engineering Chemistry.
Keywords: Liquid membrane; Rare earths; Synergistic separation; Yttrium